"Oh yeah, I'm a skateboarder" : exploring how girls in Auckland become members of the skate community : a thesis presented in partial fulfilment of the requirements for the degree of Master of Health Science in Environmental Health at Massey University, New Zealand - Collins, Jacquelyn Anne (Massey University, 2021)
Youth inactivity is a global concern, and girls are a focus of many interventions because traditional opportunities to engage in sport do not appear to meet their needs. Girls' opportunities to be active are affected by a complex network of sociocultural factors including gender role socialisation, objectification, sexism, and the male coding of many sports and physical activities. This thesis presents research based on hermeneutic phenomenological principles that explores the lived experiences of female skateboarders in Auckland, New Zealand. The multifaceted study focuses on novice female skateboarders and Girls Skate NZ, the girls-only skate school that has brought many girls into the skate community since 2018. Drawing on a focus group with skateboarding girls, interviews with the girls' parents, interviews with adult skateboarders, and quantitative skate park observations, the study investigates what it is like for girls to enter the male-dominated world of skateboarding. The study identified impeding factors to girls' skateboarding, but also that Girls Skate NZ supports girls to overcome barriers to participation and increases their confidence on and off the skate park. Parents reported that learning to skate has enhanced their daughters' resilience and given them opportunities to embrace alternative forms of femininity. The study participants reported that members of the skate community at the skate parks used by study participants have become increasingly accepting of female skateboarders. Although gendered barriers still exist that make it more challenging for girls to become skateboarders, the skate park experiences of the girls suggested that they had not experienced deliberate marginalisation from male skateboarders. Girls Skate NZ was shown to successfully provide opportunities for autonomy and competence-building in a supportive, female-friendly environment, which provides a useful blueprint for future initiatives intended to scaffold girls into male-dominated sports.
Keywords: skateboarding; gender; female skateboarding; gender role socialisation; gender stereotypes; 440509 Women's studies (incl. girls' studies)